Prospects for Mobile Health in Pakistan and Other Developing Countries - Burney, Aqil; Abbas, Zain; Mahmood, Nadeem; Arifeen, Qamar-ul (Scientific Research Publishing, 2013)
akistan is a developing country with more than half of its population located in rural areas. These areas neither have sufficient health care facilities nor a strong infrastructure that can address the health needs of the people. The expansion of Information and Communication Technology (ICT) around the globe has set up an unprecedented opportunity for delivery of healthcare facilities and infrastructure in these rural areas of Pakistan as well as in other developing countries. Mobile Health (mHealth)—the provision of health care services through mobile telephony—will revolutionize the way health care is delivered. From messaging campaigns to remote monitoring, mobile technology will impact every aspect of health systems. This paper highlights the growth of ICT sector and status of health care facilities in the developing countries, and explores prospects of mHealth as a transformer for health systems and service delivery especially in the remote rural areas.
Keywords: Mobile Health; Telemedicine; eHealth; mHealth; ICT; Heath Care in Pakistan